FUNCTIONING OF PRODUCTION AND SALES SYSTEMS AS A COMPONENT OF THE ECONOMIC POTENTIAL OF THE ENTERPRISE - Oneshko , Svitlana (Collection of scientific papers «ΛΌГOΣ», 2022)
The National Economic Strategy, proposing the development of Ukrainian industry based on the concept of "Industry 4.0" (direction 10), states that "there is a break in production chains and the loss of part of the sales markets, which leads to a drop in production volumes" and sets one of the tasks of increasing the efficiency of industrial enterprises on the basis of: "incentives for enterprises to take measures to systematically improve work efficiency; promoting the creation of the most complete production cycle; revision of existing permitting procedures in the field of industry" [1].